Education and Income in a Matrilineal Society : A Household Level Analysis - Shullai, Kenny R.; Panda, Bhagirathi (Arthshastra Indian Journal of Economics & Research, 2024)
Purpose : The study aimed to examine the relationship between parents’ educational levels and income. Education is positively related to income — whether it is the case of a developed or developing country. Educational qualifications signal the acquisition of skills and knowledge, and those with low educational qualifications are limited to participating in the formal job market with higher income. The importance of education in determining income induced us to examine the relationship in the context of a matrilineal society of Meghalaya, taking parents’ profiles and annual household income as variables of interest. Methodology : Along with the annual household income, significant variables pertaining to parents’ profiles were examined. The data were examined using binary logistic regression and descriptive statistics. Binary logistic regression uses the household’s attributes (a low-income household) as the dependent binary variable and the parents’ profile (age and education) as the independent binary variable. We conducted the analysis using SPSS for the study; a semi-structured questionnaire was used; 407 households were surveyed in Jowai and Shillong. Findings : We found that low household income was associated with parents’ educational level. Mothers’ educational level strongly determined household income in the matrilineal society of Meghalaya. The effect was almost double that of the father. Furthermore, we found that as the mother’s age increased, there was less likelihood for a household to be at a low-income level. Practical Implications : Skill development should be the primary focus of policymakers, particularly for mothers who are from poor households and have low education. Working mothers should be encouraged to pursue better career prospects through continuous adult education. Skill development aimed at mothers living in low-income households will give them the ability to improve their family’s economic situation, which will have a positive effect on human development in general. Originality : The individual impact of parents’ education on household income in the context of a matrilineal society where the mother plays a significant role in the socio-economic dynamics of a household has not been taken into account in previous studies.